2021
DOI: 10.3390/su131910793
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dynamics of Human–Wildlife Conflicts in North-Western Pakistan: Implications for Sustainable Conservation

Abstract: The high economic costs of human–wildlife conflicts (HWC) hinder long-term conservation successes, especially in developing countries. We investigated HWC by interviewing 498 respondents from 42 villages in Nowshera district, Pakistan. According to respondents, six species—the common leopard (Panthera pardus), grey wolf (Canis lupus), golden jackal (Canis aureus), red fox (Vulpes vulpes), Indian porcupine (Hystrix indica), and wild boar (Sus scrofa)—were involved in livestock predation and crop-raiding. Livest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 73 publications
5
28
0
Order By: Relevance
“…Our results further revealed that the second most influential factor was ch_2010da (chicken density). It has been reported that poultry is one of the primary sources of income for rural farmers and locals in the Nowshera district, and the red fox was held accountable for an average yearly economic loss of USD 360 (PKR 57,240)predating poultry (Khattak et al, 2021). The significant role of ch_2010da (chicken density) in red fox habitat selection in the current study agrees with Khattak et al (2021).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results further revealed that the second most influential factor was ch_2010da (chicken density). It has been reported that poultry is one of the primary sources of income for rural farmers and locals in the Nowshera district, and the red fox was held accountable for an average yearly economic loss of USD 360 (PKR 57,240)predating poultry (Khattak et al, 2021). The significant role of ch_2010da (chicken density) in red fox habitat selection in the current study agrees with Khattak et al (2021).…”
Section: Discussionsupporting
confidence: 82%
“…forests, shrubs, water bodies, herbaceous and sparse vegetation, etc. (Khattak et al, 2021). Our results showed that level 14 of glc2009 (rainfed croplands) had the highest significant contribution (Fig.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Any species causing economic losses is usually referred to as a pest animal. This undesirable feature of wildlife is the basic element of the hostile confrontation between humans and wildlife—known as human–wildlife conflicts (HWCs) [ 2 ]. HWCs mostly occur in rural areas and are primarily manifested in agricultural areas [ 3 ].…”
Section: Introductionmentioning
confidence: 99%